Prophylactic antibiotic regimens in tumour surgery (PARITY): protocol for a multicentre randomised controlled study. Issue 6 (28th November 2012) - Ghert, Michelle; Deheshi, Benjamin; Holt, Ginger; Randall, R Lor; Ferguson, Peter; Wunder, Jay; Turcotte, Robert; Werier, Joel; Clarkson, Paul; Damron, Timothy; Benevenia, Joseph; Anderson, Megan; et al.
Abstract : Introduction: Limb salvage with endoprosthetic reconstruction is the standard of care for the management of lower-extremity bone tumours in skeletally mature patients. The risk of deep postoperative infection in these procedures is high and the outcomes can be devastating. The most effective prophylactic antibiotic regimen remains unknown, and current clinical practice is highly varied. This trial will evaluate the effect of varying postoperative prophylactic antibiotic regimens on the incidence of deep infection following surgical excision and endoprosthetic reconstruction of lower-extremity bone tumours. Methods and analysis: This is a multicentre, blinded, randomised controlled trial, using a parallel two-arm design. 920 patients 15 years of age or older from 12 tertiary care centres across Canada and the USA who are undergoing surgical excision and endoprosthetic reconstruction of a primary bone tumour will receive either short (24 h) or long (5 days) duration postoperative antibiotics. Exclusion criteria include prior surgery or infection within the planned operative field, known colonisation with methicillin-resistant Staphylococcus aureus or vancomycin-resistant Enterococcus at enrolment, or allergy to the study antibiotics. The primary outcome will be rates of deep postoperative infections in each arm. Secondary outcomes will include type and frequency of antibiotic-related adverse events, patient functional outcomes and quality-of-life scores, reoperation and mortality. Randomisation will be blocked, with block sizes known only to the methods centre responsible for randomisation, and stratified by location of tumour and study centre. Patients, care givers and a Central Adjudication Committee will be blinded to treatment allocation. The analysis to compare groups will be performed using Cox regression and log-rank tests to compare survival functions at α=0.05. Ethics and dissemination: This study has ethics approval from the McMaster University/Hamilton Health Sciences Research Ethics Board (REB# 12-009). Successful completion will significantly impact on clinical practice and enhance patients' lives. More broadly, this trial will develop a network of collaboration from which further high-quality trials in Orthopaedic Oncology will follow.